Triple-shrine Temple to the northwest of Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
A Triple-shrine temple cluster, facing east, stands near the Mahanaleshwar Temple. According to Michael W. Meister, this cluster is one of the earliest temples in the Mahanaleshwar temple complex. Based on style, the north and south shrines from this triple shrine belong to the 8th century CE. Meister argues that the central shrine from the triple shrine was a later period addition. The construction material for the older two shrines is completely different from that of the central shrine. The red sandstone of the central shrine is similar to other monuments in the Mahanaleshwar temple complex. The older shrines have been reassembled as part of the restoration work undertaken by the Archaeological Survey of India (ASI).